Cultivating Conversation: Exploring Mentorship Perspectives and Experiences of Agricultural Communications Alumnae - Lauren Quinlan; Dwayne Cartmell; Audrey E. H. King; Lauren L Cline (Journal of Applied Communications, 2025)
The growth of the agricultural communications field, combined with the predicted increase in young professionals pursuing careers within agriculture, creates a need to explore how to support these professionals. This study sought to explore and describe mentorship perspectives and experiences of alumnae from [UNIVERSITY]’s agricultural communications program. It was framed by social capital theory and data collection consisted of two phases. First, a prescreening Qualtrics form was distributed via Facebook. Respondents (n = 85) provided demographic data and answered questions related to their involvement, experiences, and the extent to which they received mentorship. A non-probabilistic, purposive sampling approach was then used to select participants eligible to participate in a follow-up interview (n = 71). Ten females from this pool were interviewed to examine their pursuit of mentorship, the nature of their mentoring relationships and experiences, outcomes they received from being mentored, and how they see mentorship being discussed and facilitated. Findings imply agricultural communications alumnae are being mentored primarily through informal and natural relationships. The structure of their company or organization either positively or negatively affected their ability to receive mentorship. Agricultural communications alumnae are more likely to seek mentors they perceive as similar in terms of life stages, interests, and experiences. To spark further discussion, agricultural communications alumnae recognized a need to continue showcasing the range of mentorship-related opportunities available.
Keywords: mentorship; agricultural communications; female